Sustainable and long-term management of municipal solid waste: A review - Adewale S. Bello (17563080) (2022)
This study investigates landfill and incineration waste management strategies as potential and prevalent traditional methods of disposing of municipality-generated waste because of their cheapness and simplicity but requires a high level of management to mitigate their negative impacts. Interestingly, sustainability in municipal solid waste (MSW) is no longer limited to cleaning, uninterrupted operation, and sanitation but entails a bigger picture of a global view of ensuring environmental protection, social balance, economic stability, and a sustainable environment. The review further examined pollutant partitioning for a better understanding of the movement of hydrophobic colloids with different phases such as marine, groundwater, and soil as a factor to be considered when selecting a sustainable MSW management option. Furthermore, the incorporation of cleaner production in any waste management method has contributed immensely to the enhancement of environmental sustainability and cleaner bioresources by tackling the emergence of any environmental depletion that is likely to arise. Other Information Published in: Bioresource Technology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biteb.2022.101067